Multifunctional agriculture as a paradigm for Europe - Adornato, Francesco (Przegląd Prawa Rolnego, 2022)
The subject under consideration is multifunctional agriculture as a paradigm for Europe. The role of the function of agriculture has undergone changes that have gone well beyond food production. In particular, landscape and environmental protection issues have emerged as a result of the combination of social and cultural aspects and the urban-rural relationship. At the EU level, new paths for agriculture have developed in relation to food, the environment, climate and animal welfare.